2013
DOI: 10.2319/090212-704.1
|View full text |Cite
|
Sign up to set email alerts
|

Eruption of the permanent maxillary canines in relation to mandibular second molar maturity

Abstract: Objective: To evaluate the timing of spontaneous maxillary canine eruption in relation to stages of mandibular second molar maturation. Potential confounding effects from such factors as age, growth phase, and facial features were also explored. Subjects and Methods: A sample of 106 healthy subjects (48 females and 58 males; age range, 9.4-14.3 years) with both permanent maxillary canines during the final phase of intraoral eruption were included. Mandibular second molar maturation (stages E to H) was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Several studies have assessed the relationship between facial heights and skeletal maturity. 5,12,13,15,16 This study evaluated skeletal maturity and dental maturity and compared them in low-angle and high-angle females and males. The groups of this study were categorized based on the mandibular plane angle, because the mandibular plane angle is a simple and reliable analytical tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have assessed the relationship between facial heights and skeletal maturity. 5,12,13,15,16 This study evaluated skeletal maturity and dental maturity and compared them in low-angle and high-angle females and males. The groups of this study were categorized based on the mandibular plane angle, because the mandibular plane angle is a simple and reliable analytical tool.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 Moreover, it is also known that there is a relationship between vertical growth direction and skeletal maturity. 5,12,13,15,16 Baccetti et al 5 stated that eruption of teeth completed an earlier stage in hyperdivergent subjects. Perinetti et al 15 also found that patients with a vertical facial type had earlier dental maturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est dans ce contexte que la méthode de maturation des vertèbres cervicales (CVM) a été initialement introduite par Lamparski (1972) pour l'évaluation de la maturation squelettique, en exploitant une simple téléradiographie de profil faisant partie du bilan orthodontique standard [1,7]. Actuellement, la méthode CVM est largement répan-due en orthodontie, et suscite un intérêt majeur de la part des cliniciens dans l'évaluation de la maturation squelettique [1,[8][9][10][11][12][13]. Ce travail a pour objectif d'apporter une mise au point sur la méthode CVM afin de montrer son intérêt par rapport à la méthode de radiographie de la main.…”
Section: Résuméunclassified
“…Transverse maxillary deficiency is associated with maxillary canine impaction (6)(7)(8); thus, early interceptive orthodontic treatment with rapid maxillary expansion is effective in increasing the eruption rate of displaced maxillary canines (9)(10)(11). In the absence of such treatment, maxillary canine impaction requires comprehensive orthodontic-surgical treatment, including surgical exposure of the canine crown and orthodontic traction to bring the impacted canine into occlusion (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%